Cardiovascular risk in systemic sclerosis: Micro- and Macro-vascular involvement - Eleni Pagkopoulou; Marina Poutakidou; Alexandros Garyfallos; George Kitas; Theodoros Dimitroulas (Indian Journal of Rheumatology)
Systemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis of multiple organs (kidney, heart, lung, gastrointestinal tract, and skin), endothelial damage leading to vascular disease, and autoantibody production. Although the microvascular disease is well-understood, mechanistic insights explaining the presence and extent of macrovascular disease in SSc patients has been a matter of intense debate, especially in the past few years. Patients with systemic sclerosis have an increased risk for atherosclerotic cardiovascular disease (CVD), possibly mediated by inflammatory and fibrotic mechanisms. The excess cardiovascular risk in SSc is suggested by increased arterial stiffness, carotid intima thickening, and reduced flow-mediated dilatation. Given the involvement of the microvasculature, the differentiation between primary and ischemic heart disease is difficult. There is a relative paucity of data regarding clinical and preclinical CVD in SSc. Therefore, large cohort studies are required to clarify whether CVD is predominantly associated with atherosclerosis or microvascular involvement. The aim of this review is to discuss primary and ischemic heart disease and their contribution to CVD in SSc.